Notice of Removal: Microbubble localization errors in ultrasonic super-resolution imaging - Jeffries,KC; Harput,S; Brown,J; Dunsby,C; Aljabar,P; Tang,MX; Eckersley,R (2017)
Recently, acoustic super-resolution (SR) imaging has allowed visualization of microvascular structure and flow beyond the diffraction limit through the localization of many isolated microbubble signals. Each bubble position is typically estimated by calculating the centroid, finding a local maximum, or finding the peak of a 2-D Gaussian function fit. However, the backscattered signal from a microbubble depends not only on diffraction characteristics of the waveform, but also on the bubble behavior in the acoustic field, which if not accounted for, may cause localization errors.